Efektivitas Formulasi Baiting Buah Bintaro (Cerbera manghas) Terhadap Kematian Tikus Mencit Putih - Adila Rizki Hidayah; Nur Utomo; Mela Firdaust; Hari Rudijanto IW; Fauzan Ma'ruf (Poltekkes Kemenkes Semarang, 2026)
In 2023, Banyumas reported the third-highest leptospirosis cases in Central Java, underscoring the need for effective rodent control. This study evaluates bintaro fruit (Cerbera manghas) as a botanical rodenticide, leveraging its toxic compound, cerberin, known to be lethal to rodents. The objective was to assess the effectiveness of bait formulations containing bintaro fruit on the mortality rate and time of death of albino mice (Mus musculus albino). A true experimental design with a post-test control group was conducted, involving 22 male white mice divided into a control group and four treatment groups (15g, 20g, 25g, and 30g doses), each with five replications. The bait was formulated with fish meal, bran, and candlenut. The Kruskal-Wallis test and Probit regression were used to analyze the effects of dosage on mortality and to estimate the LD₅₀. Results indicated an 80% mortality rate at a 30g dose, with a trend of reduced time to death as dosage increased. However, the Kruskal-Wallis test revealed no significant differences in mortality rate (p = 0.554) or time of death (p = 0.248) among dosage treatments. The Probit regression analysis determined an LD₅₀ value of 18.23 grams. These findings highlight the potential of bintaro fruit as a plant-based rodenticide. Further research is recommended to conduct phytochemical analyses and refine dosage testing.